Probe-based qPCR assay enables the rapid and specific detection of bacterial degrading genes for the pesticide metaldehyde in soil - Castro Gutiérrez, Víctor Manuel (2022)
Metaldehyde, a molluscicide pesticide, has been identified as a pollutant of concern due to its repeated detection in drinking water, thereby generating numerous compliance failures for water utilities. Biological degradation potential for metaldehyde is widespread in soils, occurring at different rates, but to date, no molecular methods for its assessment have been reported. Here, three genes belonging to a shared metaldehyde-degrading gene cluster present in bacteria were used as candidates for development of a quantitative PCR (qPCR) assay for assessing the metaldehyde-degrading potential in soil. Screening of gene targets, primer pairs and optimization of reaction conditions led to the development of a sensitive and specific probe-based qPCR method for quantifying the mahY metaldehyde-degrading gene from soil. The technique was tested across 8 soils with different compositions and origins. The degrading pathway was detected in 4/8 soils, in which a higher number of gene copies correlated with periods of greater metaldehyde removal. Additionally, swift elimination of the pesticide was observed in soils with an elevated initial number of mahY gene copies. The gene cluster was not detected in other soils, even though metaldehyde removal occurred, indicating that other biological degrading pathways are also important in nature. The method described here is the first one available to estimate the microbial metaldehyde degradation potential and activity in soils, and can also be used to detect degrading microorganisms in systems such as sand filters for water purification or to monitor degrading strains in engineered processes. Previous article in issue